2016
DOI: 10.1371/journal.pmed.1001967
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Treatment with Favipiravir for Ebola Virus Disease (the JIKI Trial): A Historically Controlled, Single-Arm Proof-of-Concept Trial in Guinea

Abstract: BackgroundEbola virus disease (EVD) is a highly lethal condition for which no specific treatment has proven efficacy. In September 2014, while the Ebola outbreak was at its peak, the World Health Organization released a short list of drugs suitable for EVD research. Favipiravir, an antiviral developed for the treatment of severe influenza, was one of these. In late 2014, the conditions for starting a randomized Ebola trial were not fulfilled for two reasons. One was the perception that, given the high number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
369
1
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 417 publications
(396 citation statements)
references
References 51 publications
12
369
1
14
Order By: Relevance
“…Importantly, the rVSV vaccine work in Guinea shows how a clinical trial can be done effectively during an outbreak, in contrast to clinical trials for ZMapp 151 , favipiravir 172 and TKM-130803 (REF. 156), which were important for compassionate use but were not wellconducted clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, the rVSV vaccine work in Guinea shows how a clinical trial can be done effectively during an outbreak, in contrast to clinical trials for ZMapp 151 , favipiravir 172 and TKM-130803 (REF. 156), which were important for compassionate use but were not wellconducted clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…For favipiravir, oral administration is a major benefit in resource-poor settings. Clinical trials of favipiravir in West Africa suggested some benefit in patients with lower viral loads when treatment was initiated 172 . Favipiravir was safe in phase I trials as well as in a clinical trial in patients with EBOV infection 172 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mortality rate of 54% in those who received favipiravir was not statistically different than the mortality rate of 58% among Bhistoric^controls from the same outbreak and area that the authors used for analysis [51]. The authors suggest that those who received favipiravir and had a higher pretreatment CT value had a lower mortality than historic controls; however, they also note that the study was not adequately powered or designed to detect such an effect.…”
Section: Antiviral Therapeuticsmentioning
confidence: 82%